Functional capacity, health impact, and risk of sarcopenia in individuals with chronic obstructive pulmonary disease. - Janine Bosi Tonel; Maitê Mendes Pellenz; Maria Elaine Trevisan; Ariovaldo Leal Fagundes; Luciane Flores Jacobi (Acta Scientiarum. Health Sciences, 2025)
This study aimed to verify the functional capacity of individuals with chronic obstructive pulmonary disease (COPD) and its associated factors. This study is a cross-sectional, observational study with quantitative data analysis. It was performed with patients previously diagnosed with any degree of COPD: I (mild), II (moderate), III (severe), and IV (very severe). Functional capacity was assessed using the six-minute step test (6MST), the risk for sarcopenia was identified using the SARC-F + CC questionnaire, and the clinical impact of COPD was quantified using the COPD Assessment Test (CAT) questionnaire. Moreover, primary data were collected from the patients to identify associated factors. The results of the 37 patients evaluated (59.5% female; 81.1% elderly), 30 (81.1%) had reduced functional capacity. Out of these, 53.3% were at risk for sarcopenia and 93.3 % were somehow clinically impacted by COPD. Their impact was classified into mild to moderate (53.3%) and severe and very severe (40%). Furthermore, most patients (60%) had a recent diagnosis and almost all of them (96.7%) were smokers or former smokers. In conclusion, most patients had reduced functional capacity which was significantly associated with dyspnea and risk of sarcopenia.